Original paperDistribution of Malassezia species in patients with atopic dermatitis – quality assessment - Rup, Elżbieta; Skóra, Magdalena; Krzyściak, Paweł; B. Macura, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: The fungi Malassezia are a constituent of the skin microbiota in humans and some animals. The fungi may cause skin diseases or even organ and/or generalized infections in the presence of appropriate predisposing factors. Aim: To evaluate the occurrence of Malassezia fungi on the skin in patients with psoriasis and search for a relationship between the occurrence of Malassezia and the severity of skin lesions, age and sex of the patients. Material and methods: The materials comprised smears sampled from four sites: scalp, face, chest and back. Malassezia spp. were isolated in cultures on modified Dixon medium and identified on the basis of morphological and biochemical features. Results: Malassezia spp. were isolated in 55.1% of the patients. The fungi were most prevalent on the back (33.3%) and least on the scalp (17.5%) and face (19%). The prevalence on the chest was 30.2%. In the group of patients with AD localized to the head and neck Malassezia spp. were cultured in 71.4% of patients. Conclusions: No statistically significant differences were found between Malassezia prevalence in males vs. females. No relationship with the patients’ age was found. Higher values of the atopic dermatitis severity index (SCORAD) were found in the patients in whom Malassezia spp. were isolated. Malassezia spp. were particularly common in the group of patients with AD localized to the head and neck